Hydrochemical process and controls on the hydrochemistry of river water in the Muling-Xingkai Plain, Northeast China - Su, Chen; Liu, Yuan; Cheng, Zhongshuang; Wang, Wenzhong; Zheng, Zhaoxian (Frontiers in Environmental Science, 2022)
Rivers are the main supply sources in inland areas for human activities, but they are also regarded as the most susceptible water bodies to pollutants. Understanding the key factors influencing the chemical characteristic is the basis for water supply and public health concern. And it is helpful for the protection of surface water under the influence of human activities. To reveal the hydrochemical process of river water and the key factors affecting the chemical compositions, a total of 33 samples from rivers in Muling-Xingkai Plain are collected for principal component analysis and hydrochemical analysis. Results indicate that river water is characterized by the type of HCO3-Ca and mixed HCO3-Ca·Na. But some samples with relative high nitrate content have Cl− as the dominant anion. The natural sources of chemical ions in river water are silicate and carbonate minerals. The chemical fertilizers only slightly influence the chemical compositions of river water due to the retardation of black soil with weak permeability. The chemical compositions of river water in Muling river are significantly influenced by domestic sewage compared with that in Abuqin river and Qihulin river. The widespread thick black soils play a key roles in protecting the river quality and groundwater quality, and human activities only play a limited roles in determining the river quality in the Muling-Xingkai Plain. At present, the contents of major chemical ions in river water meet the irrigation standard. Although the irrigation with river water do not lead to the food safety issue, the government agencies should adopt adequate measures to control the indiscriminate discharge of domestic sewage and application of fertilizers for preventing the accumulation of pollutants in rivers. This study is beneficial to the efficient management of surface water resources in agricultural areas with similar geological conditions and hydrogeological conditions.